Neurointensive care unit system for continuous electrophysiological monitoring with remote web-based review. - Van der Kouwe, A.J.W (IEEE Transactions on information technology in biomedicine)
There is a need in the neurological intensive care unit for a single integrated bedside monitor for continuously monitoring the function of the patient's central nervous system. In this paper, we demonstrate the feasibility of building such a system and operating it in the intensive care environment. We have developed a fully automated system that samples electrophysiological waveforms of various modalities according to a schedule of predefined intervals along with routinely monitored cardiac and respiratory parameters. The system provides stimulation and acquires responses without requiring supervision. The electrophysiological data include brainstem auditory and somatosensory evoked potentials and epochs of the electroencephalogram. The system applies peak detection and spectral analysis to extract salient parameters from the raw waveforms. The results are made available immediately in real time on the local network for local review and further analysis. A Web-based interface makes review by a qualified neurologist possible anywhere within the hospital's secure intranet during and after monitoring. This system could potentially give an early warning of impending herniation, subclinical seizures, and brain or spinal cord ischemia. We demonstrate its application in a few diverse neurological intensive care cases and a case in the interventional neuroradiology suite.